2021
DOI: 10.1111/pbi.13589
|View full text |Cite
|
Sign up to set email alerts
|

Spray‐induced gene silencing for disease control is dependent on the efficiency of pathogen RNA uptake

Abstract: Summary Recent discoveries show that fungi can take up environmental RNA, which can then silence fungal genes through environmental RNA interference. This discovery prompted the development of Spray‐Induced Gene Silencing (SIGS) for plant disease management. In this study, we aimed to determine the efficacy of SIGS across a variety of eukaryotic microbes. We first examined the efficiency of RNA uptake in multiple pathogenic and non‐pathogenic fungi, and an oomycete pathogen. We observed efficient double‐strand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 70 publications
(90 reference statements)
5
151
0
Order By: Relevance
“…It is well established that spraying plants with dsRNAs and siRNAs encoding key genes of plant pathogenic fungi [16][17][18][19][20][21] and viruses [22][23][24][25][26][27] effectively reduces development of the pathogens and suppresses the infection process. These externally applied dsRNAs and siRNAs have been shown to spread systemically into plant tissues and were uptaken by the fungal cells inducing a RNAi-mediated silencing of the targeted genes of the pathogens [16,17,21,27]. This strategy of plant disease control was termed as spray-induced gene silencing (SIGS) and is currently considered as an efficient and sustainable plant protection strategy and for other crop improvement strategies [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that spraying plants with dsRNAs and siRNAs encoding key genes of plant pathogenic fungi [16][17][18][19][20][21] and viruses [22][23][24][25][26][27] effectively reduces development of the pathogens and suppresses the infection process. These externally applied dsRNAs and siRNAs have been shown to spread systemically into plant tissues and were uptaken by the fungal cells inducing a RNAi-mediated silencing of the targeted genes of the pathogens [16,17,21,27]. This strategy of plant disease control was termed as spray-induced gene silencing (SIGS) and is currently considered as an efficient and sustainable plant protection strategy and for other crop improvement strategies [29].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies that show induction of plant fungal [16][17][18][19][20][21] and viral [22][23][24][25][26][27] resistance after external application (spraying or mechanical inoculation) of dsRNAs, siRNAs, or hpRNAs designed to target virulence-related genes of the pathogens. Recent studies have also provided evidence that both plants and infecting pathogens were capable of the RNA uptake, and this eventually triggered RNAi-mediated silencing of the pathogen virulence-related genes [16,17,21,22,27]. Exogenously induced RNAi has recently emerged as a strategy with a potential to protect plants from microbial diseases, viral infections, and invading insects [9,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, SIGS against Sclerotinia sclerotium and Botrytis cinerea on oilseed rape and Arabidopsis thaliana, and against F. asiaticum on wheat resulted in reduced fungal disease (McLoughlin et al 2018, Song et al 2018. A recent study also showed that SIGS can also be applied against the basidiomycete fungus Rhizoctonia solani to control sheath blight of rice (Qiao et al 2021). In this study, topical application of dsRNA targeting vesicle trafficking pathway genes DYNACTIN 1 (DCN1) and SUPPRESSOR OF ACTIN 1 (SAC1), or a gene coding for polygalacturonase (a known virulence factor gene of R. solani) resulted in a significant reduction of fungal biomass and disease symptoms on rice plants (Qiao et al 2021).…”
Section: Sigs To Control Fungal and Oomycete Plant Pathogensmentioning
confidence: 98%
“…In addition to mediating a broad range of cellular processes related to growth and development, roles for sRNAmediated RNAi in host-pathogen interactions have been described (Chaloner et al 2016, Qiao et al 2021. While most sRNAs function endogenously, some sRNAs move bidirectionally from one species to another and modulate cellular functions of recipient cells by regulating their gene expression through targeted gene silencing (Weiberg et al 2013, Chaloner et al 2016, Cai et al 2018.…”
Section: Sigs In Crop Protectionmentioning
confidence: 99%
“…Recent discovery of fungal RNA uptake makes SIGS possible to control fungal diseases in crops 41,55,62 . SIGS approaches have been successfully used to prevent fungal infections in both monocot and dicot plants, as well as in post-harvest materials 41,54,55 .…”
Section: Accepted Articlementioning
confidence: 99%